2011
DOI: 10.4103/0019-5049.89880
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate depth of placement of oral endotracheal tube and its possible determinants in Indian adult patients

Abstract: Background:Optimal depth of endotracheal tube (ET) placement has been a serious concern because of the complications associated with its malposition.Aims:To find the optimal depth of placement of oral ET in Indian adult patients and its possible determinants viz. height, weight, arm span and vertebral column length.Settings and Design:This study was conducted in 200 ASA I and II patients requiring general anaesthesia and orotracheal intubation.Methods:After placing the ET with the designated black mark at voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 10 publications
0
41
1
12
Order By: Relevance
“…[14][15][16][17]19] According to Simpson et al, [14] capnography should be used to confirm ETT position in all intubations, including those performed outside the operating theatre. [13] Delorio [15] confirmed that capnography is the recommended method for ETT verification, but also recognised that the use of capnography is limited and is often either not available or inconsistently applied in ETT verification. Dittrich [16] confirmed that capnography is the most reliable method for verification of the ETT.…”
Section: Capnographymentioning
confidence: 99%
See 4 more Smart Citations
“…[14][15][16][17]19] According to Simpson et al, [14] capnography should be used to confirm ETT position in all intubations, including those performed outside the operating theatre. [13] Delorio [15] confirmed that capnography is the recommended method for ETT verification, but also recognised that the use of capnography is limited and is often either not available or inconsistently applied in ETT verification. Dittrich [16] confirmed that capnography is the most reliable method for verification of the ETT.…”
Section: Capnographymentioning
confidence: 99%
“…However, when all three bedside methods were combined, sensitivity was higher than observing the centimetre scale alone. Varshney et al [13] reported in their study that the centimetre scale printed on the ETT could be used as a verification method. They suggested that optimal depth of the ETT placement could be estimated by means of a formula: height in cm/7 -2.5.…”
Section: Using Centimetre Scale Printed On the Ettmentioning
confidence: 99%
See 3 more Smart Citations